The emergent neurosurgical outcome of spontaneous intracranial hemorrhage in patients with chronic liver disease - Tze-Wei Chang; Kuan-Ting Robin Lin; Sheng-Tzung Tsai; Chien-Hui Lee (Tzu-Chi Medical Journal, 2023)
Objectives: The influence of chronic liver disease (CLD) on emergent neurosurgical outcomes in patients with spontaneous intracerebral hemorrhage (ICH) remains unclear. CLD is usually associated with coagulopathy and thrombocytopenia, which contribute to a high rebleeding rate and poor prognosis after surgery. This study aimed to confirm the outcomes of spontaneous intracranial hemorrhage in patients with CLD after emergent neurosurgery. Materials and Methods: We reviewed the medical records of all patients with spontaneous ICH from February 2017 to February 2018 at the Buddhist Tzu Chi Hospital, Hualien, Taiwan. This study was approved by the Review Ethical Committee/Institutional Board Review of Hualien Buddhist Tzu Chi Hospital (IRB111-051-B). Patients with aneurysmal subarachnoid hemorrhage, tumors, arteriovenous malformations, and those younger than 18 years were excluded. Duplicate electrode medical records were also removed. Results: Among the 117 enrolled patients, 29 had CLD and 88 did not. There were no significant differences in essential characteristics, comorbidities, biochemical profile, Glasgow coma scale (GCS) score at admission, or ICH sites. The length of hospital stay (LOS) and length of intensive care unit stay (LOICUS) are significantly longer in the CLD group (LOS: 20.8 vs. 13.5 days, P = 0.012; LOICUS: 11 vs. 5 days, P = 0.007). There was no significant difference in the mortality rate between the groups (31.8% vs. 28.4%, P = 0.655). The Wilcoxon rank-sum test for liver and coagulation profiles between survivors and the deceased revealed significant differences in the international normalized ratio (P = 0.02), including low platelet counts (P = 0.03) between survivors and the deceased. A multivariate analysis of mortality found that every 1 mL increase in ICH at admission increased the mortality rate by 3.9%, and every reduction in GCS at admission increased the mortality rate by 30.7%. In our subgroup analysis, we found that the length of ICU stay and LOS are significantly longer in patients with CLD who underwent emergent neurosurgery: 17.7 ± 9.9 days versus 7.59 ± 6.68 days, P = 0.002, and 27.1 ± 7.3 days versus 16.36 ± 9.08 days, P = 0.003, respectively. Conclusions: From our study's perspective, emergent neurosurgery is encouraged. However, there were more prolonged ICU and hospital stays. The mortality rate of patients with CLD who underwent emergent neurosurgery was not higher than that of patients without CLD.